(untitled) (Global Journal of Science Frontier Research, 2020)
In the article the survey of the existing constructions of high-voltage electrostatic generators is carried out. Are described the new types of the generators of Mende, the using laws of electrostatic induction and the tests of the experimental are carried out the models of such generators.